2014
DOI: 10.1016/j.ygyno.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Taselisib, a selective inhibitor of PIK3CA, is highly effective on PIK3CA-mutated and HER2/neu amplified uterine serous carcinoma in vitro and in vivo

Abstract: Objective To evaluate the efficacy of Taselisib, a selective inhibitor of PIK3CA, against primary uterine serous carcinomas (USC) harboring PIK3CA mutations and HER2/neu gene amplification. Methods Sensitivity to taselisib was evaluated by flow-cytometry viability assays in vitro against nine primary USC cell lines. Cell cycle distribution and downstream signaling were assessed by measuring the DNA content of cells and by phosphorylation of the S6 protein by flow-cytometry. Preclinical efficacy of taselisib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…The effect of single agent neratinib and taselisib on the viability of 3 primary USC cell lines (i.e., USPC-ARK-2, 20, 21) has been previously reported (23, 27). The effect of neratinib on the viability and IC 50 of USPC-ARK-1 cell line was determined in flow-cytometry based assays as previously described (23, 27).…”
Section: Methodsmentioning
confidence: 90%
“…The effect of single agent neratinib and taselisib on the viability of 3 primary USC cell lines (i.e., USPC-ARK-2, 20, 21) has been previously reported (23, 27). The effect of neratinib on the viability and IC 50 of USPC-ARK-1 cell line was determined in flow-cytometry based assays as previously described (23, 27).…”
Section: Methodsmentioning
confidence: 90%
“…These findings have prompted numerous pre-clinical studies that have demonstrated that PI3K inhibition can impair the proliferation of endometrial cancer cells and that loss of PTEN or PIK3CA mutation may serve as a biomarker associated with response to novel agents that antagonize PI3K [45][46][47][48]. In a large study evaluating pan PI3K inhibition, cell lines across many disease sites with a PIK3CA mutation and PTEN loss manifested the greatest sensitivity [48].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…It has been shown that 70% of HER2 gene amplified endometrial cancers harbor a concurrent gain of function mutation in PIK3CA [50]. Numerous studies have demonstrated that PIK3CA mutation uncouples in vitro and in vivo response to anti-HER2 therapies and that adding concurrent PI3K inhibition, either directly or via downstream mTOR inhibition, can restore efficacy [47,50,51].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Unlike other PIK3 inhibitors, taselisib is designed to bind the ATP-binding pocket of PI3K with selective preference for the mutated form of PIK3CA [73]. In preclinical models, taselisib caused growth inhibition in both HER2+ and PIK3CA-mutated cell lines and was highly active at reducing tumor growth in xenografts mouse harboring PIK3CA mutation and overexpressing HER2 [74]. The combination of taselisib and letrozole in a BC cell line engineered to express aromatase decreased cellular viability and increased apoptosis relative to either single agent [75].…”
Section: Taselisib (Gdc-0032)mentioning
confidence: 99%